The development of media learning using plotagon software on circle material - Eri Saputra; M Marhami; Raduan B; M Mursalin; Nur Azmi (SAINTIS Publishing, 2022)
The challenges in learning mathematics at schools could be worrying because the delivery is usually less interesting which makes students feel bored with the lesson. Mathematics from the student’s perspective is considered a scary subject because it is very difficult to understand. This study aims to determine the feasibility level of learning media using Plotagon software in Mathematics Subjects at SMA Negeri 1 Terangun. This type of study is research and development (RD). The model used in this study is the Analyze, Design, Development, Implementation, Evaluation (ADDIE) model. The subjects of this study were students of class XI IPA I SMA Negeri 1 Terangun. Data collection techniques were carried out by questionnaires and observations. The instrument used is a questionnaire using a Likert scale. The results of the study obtained were Plotagon Learning Media in the Mathematics Subject Circle material received an assessment with average score 3,36 from material experts, 3,45 from media experts, 3,80 from small group students and 3,83 from large group students. So it can be concluded that the Plotagon software learning media in the Mathematics subject matter Circle is suitable for learning at SMA Negeri 1 Terangun.